2016
DOI: 10.1136/bmjopen-2016-012537
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of treatment failure on second-line antiretroviral therapy among adults in northwest Ethiopia: a multicentre retrospective follow-up study

Abstract: BackgroundThe number of patients using second-line antiretroviral therapy (ART) has increased over time. In Ethiopia, 1.5% of HIV infected patients on ART are using a second-line regimen and little is known about its effect in this setting.ObjectiveTo estimate the rate and predictors of treatment failure on second-line ART among adults living with HIV in northwest Ethiopia.SettingAn institution-based retrospective follow-up study was conducted at three tertiary hospitals in northwest Ethiopia from March to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 31 publications
9
69
3
Order By: Relevance
“…This is in agreement with other studies conducted in developing countries that have shown that male HIV patients are more likely to present to HIV care facilities with advanced disease as compared to their female counterparts [23,24]. Moreover, studies conducted in Ethiopia and South Africa have cited advanced HIV/AIDS as a critical predictor for failure on secondline ART [25,26]. Furthermore, research has shown that males are more prone to virological failure while on second-line ART than females [27,28], attributable to poor adherence and higher odds of alcohol consumption while on ART [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with other studies conducted in developing countries that have shown that male HIV patients are more likely to present to HIV care facilities with advanced disease as compared to their female counterparts [23,24]. Moreover, studies conducted in Ethiopia and South Africa have cited advanced HIV/AIDS as a critical predictor for failure on secondline ART [25,26]. Furthermore, research has shown that males are more prone to virological failure while on second-line ART than females [27,28], attributable to poor adherence and higher odds of alcohol consumption while on ART [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…Report from one study showed that lower baseline body mass index (BMI) (AOR = 2.8; 95% CI: 1.01-7.5) [28] and patients who had height for age in the third percentile or less (AHR = 3.3; 95% CI: 1.0-10.6) [22] were more likely to expose to HIV treatment failure. On the other hand, weight change per 1 kg increase (AHR = 0.9, 95% CI: 0.9-0.9) [17], and < 50 kg weight at baseline (AHR = 0.58, 95% CI:0.38-0.89) [13] were less likely to expose to HIV treatment failure.…”
Section: Clinical-related Factorsmentioning
confidence: 99%
“…A higher viral load may lead to HIV treatment failure, which is becoming a threat of different African countries, like in Burkina Faso (6.4%) [10], Ghana (15.7%) [11], and Tanzania (14.9%) [12]. In Ethiopia, virological, immunological, and clinical failure is found in the range between 1.3% [13] to 11.5% [14], 2.1% [15] to 21% [16], and 3.1% [17] to 12.3% [18], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A higher viral load may leads to HIV treatment failure, which is becoming a threat of different African countries, like in Burkina Faso (6.4%) (12), Ghana (15.7%) (13), and Tanzania (14.9%) (14). In Ethiopia, virological, immunological, and clinical failure found to be in the range between 1.3% (15) to 11.5% (16), 2.1% (17) to 21% (18), and 3.1% (19) to 12.3% (20) respectively.…”
Section: Introductionmentioning
confidence: 99%